Risk Factors of Chronic Kidney Disease (CKD) in Type 2 Diabetes Mellitus (DM) Patients at Dr. Soetomo General Academic Hospital, Surabaya - Joshua Teofilus Sutadji; Agung Pranoto; Risky Vitria Prasetyo (Universitas Airlangga, 2023)
Highlights:1. The highest risk was a history of hypertension, followed by a history of low HDL levels.2. Patients with type 2 DM at Dr. Soetomo General Academic Hospital, Surabaya, had a greater risk of developing CKD for patients with a history of hypertension (3.801 times higher) and patients with a history of low HDL (3.356 times higher). AbstractIntroduction: Type 2 diabetes mellitus (DM), categorized as a non-communicable disease, has become a global health concern. This study aimed to identify the risk factors for chronic kidney disease (CKD) in type 2 DM patients at Dr. Soetomo General Academic Hospital, Surabaya.Methods: This was a case-control study. The samples were collected using consecutive sampling methods from the medical records Dr. Soetomo General Academic Hospital, Surabaya. The total samples were 158 patients consisting of 79 cases and 79 controls. Independent variables were a history of uncontrolled HbA1c levels; hypertension; high triglyceride (TG) levels; low high-density lipoprotein (HDL) levels, high low-density lipoprotein (LDL) levels, and being overweight. The dependent variable was CKD. Samples were analyzed using the Chi-Square test and logistic regression.Results: From six independent variables that were analyzed, two variables had significant results based on the Chi-Square test. Logistic regression was performed and showed the significant results between risk factors of CKD and type 2 DM patients at Dr. Soetomo General Academic Hospital, Surabaya, were a history of hypertension (OR = 3.801, 95% CI = 1.875-7.706) and a history of low HDL levels (OR = 3.356, 95% CI = 1.650-6.827). The highest risks were a history of hypertension followed by a history of low HDL levels.Conclusion: Type 2 DM patients at Dr. Soetomo General Academic Hospital, Surabaya, with a history of hypertension and a history of low HDL had a greater risk of developing CKD.